2021
DOI: 10.3390/biomedicines9111607
|View full text |Cite
|
Sign up to set email alerts
|

Renal Hypouricemia 1: Rare Disorder as Common Disease in Eastern Slovakia Roma Population

Abstract: Renal hypouricemia (RHUC) is caused by an inherited defect in the main reabsorption system of uric acid, SLC22A12 (URAT1) and SLC2A9 (GLUT9). RHUC is characterized by a decreased serum uric acid concentration and an increase in its excreted fraction. Patients suffer from hypouricemia, hyperuricosuria, urolithiasis, and even acute kidney injury. We report clinical, biochemical, and genetic findings in a cohort recruited from the Košice region of Slovakia consisting of 27 subjects with hypouricemia and relatives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Hitherto, we have enrolled dysuricemia (hyperuricemia and hypouricemia) individuals from the Roma populations ( Stiburkova et al, 2016 ; Toyoda et al, 2019 ; Pavelcova et al, 2020 ; Stiburkova et al, 2021 ). In this process, we serendipitously found a family with RHUC of which the proband exhibited severe phenotypes; however, its causality could not be explained by already-characterized genetic variations responsible for RHUC, as described below.…”
Section: Introductionmentioning
confidence: 99%
“…Hitherto, we have enrolled dysuricemia (hyperuricemia and hypouricemia) individuals from the Roma populations ( Stiburkova et al, 2016 ; Toyoda et al, 2019 ; Pavelcova et al, 2020 ; Stiburkova et al, 2021 ). In this process, we serendipitously found a family with RHUC of which the proband exhibited severe phenotypes; however, its causality could not be explained by already-characterized genetic variations responsible for RHUC, as described below.…”
Section: Introductionmentioning
confidence: 99%
“…There were no racial differences in exercise-induced changes in purine metabolism. As noted in the Introduction, although the frequency of RHUC is reported to be higher in the Japanese and in the Roma ethnic group, which is also distributed in the Czech Republic [ 8 ], there are no reports of differences in the symptoms of RHUC or the frequency of EIAKI.…”
Section: Discussionmentioning
confidence: 99%
“…The world’s highest frequency of predominant dysfunctional RHUC1 variants was identified in the common European Roma population (1125 subjects): the rs200104135 (p.T467M) variant has a frequency of 5.76%, and the deletion variant p.L415_G417 (no available in public databases) has a frequency of 1.73%. RHUC is asymptomatic, but it can cause clinical complications, such as exercise-induced acute kidney injury (EIAKI) and urinary tract stones [ 7 , 8 , 9 ]. The hypothesized cause of the renal failure is that RHUC with low UA is affected by ROS and causes renal ischemia due to vasoconstriction.…”
Section: Introductionmentioning
confidence: 99%
“…Among Roma populations and in Korea, where the same URAT1 mutant alleles were repeatedly identified, lower frequencies of GLUT9 mutant alleles than of URAT1 mutant alleles were reported [ 24 , 25 , 26 ]. In China, screening of the URAT1 and GLUT9 genes for mutations was performed in 31 individuals with hypouricemia (SUA concentration ≤2.0 mg/dL) selected from the general population [ 27 ], and this showed that the number of people with GLUT9 mutations was lower than that of people with URAT1 mutations (two vs. four, no mutations in the URAT1 or GLUT9 genes were found in the other 25 individuals).…”
Section: Genetic Basis For the Epidemiological Features Of Hypouricemiamentioning
confidence: 99%